DEVELOPING IMAGINATION ABOUT SPACE OF PRIMARY SCHOOL STUDENTS IN THE LEARNING PROCESS - Gulchehra Sofiboyeva (International Scientific and Current Research Conferences, 2021)
In this article, we have focused on the learning process of educators and learners. Objective: To study the current situation and the problem of improving the effectiveness of the study of geometric materials through the development of spatial imagination of primary school students in educational institutions. It's about finding the right solution to a problem.